Magnetic phase diagram of superantiferromagnetic TbCu2 nanoparticles. (23rd November 2015) - Echevarria-Bonet, C; Rojas, D P; Espeso, J I; Rodríguez Fernández, J; de la Fuente Rodríguez, M; Fernández Barquín, L; Rodríguez Fernández, L; Gorria, P; Blanco, J A; Fdez-Gubieda, M L; Bauer, E; Damay, F
Abstract: The structural state and static and dynamic magnetic properties of TbCu2 nanoparticles are reported to be produced by mechanical milling under inert atmosphere. The randomly dispersed nanoparticles as detected by TEM retain the bulk symmetry with an orthorhombic Imma lattice and Tb and Cu in the 4 e and 8 h positions, respectively. Rietveld refinements confirm that the milling produces a controlled reduction of particle sizes reaching ≃6 nm and an increase of the microstrain up to ≃0.6%. The electrical resistivity indicates a metallic behavior and the presence of a magnetic contribution to the electronic scattering which decreases with milling times. The dc-susceptibility shows a reduction of the Néel transition (from 49 K to 43 K) and a progressive increase of a peak (from 9 K to 15 K) in the zero-field-cooled magnetization with size reduction. The exchange anisotropy is very weak (a bias field of ≃30 Oe) and is due to the presence of a disordered (thin) shell coupled to the antiferromagnetic core. The dynamic susceptibility evidences a critical slowing down in the spin-disordered state for the lowest temperature peak associated with a spin glass-like freezing with a tendency of zv and exponents to increase when the size becomes 6 nm ( and ). A Rietveld analysis of the neutron diffraction patterns K, including the magnetic structure determination, reveals that there is a reduction of the expected moment (≃80%), which must be connected to the presence of the disordered particle shell. The core magnetic structure retains the bulk antiferromagnetic arrangement. The overall interpretation is based on a superantiferromagnetic behavior which at low temperatures coexists with a canting of surface moments and a mismatch of the antiferromagnetic sublattices of the nanoparticles. We propose a novel magnetic phase diagram where changes are provoked by a combination of the decrease of size and the increase of microstrain.